DIDACTIC AND METHODOLOGICAL FOUNDATIONS OF INTEGRATING DIGITAL TECHNOLOGIES IN TEACHING ENGLISH (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article explores the didactic and methodological foundations of integrating digital technologies into English language teaching. The study highlights the role of modern digital tools in improving students’ language skills, increasing motivation, and creating interactive learning environments. Special attention is given to innovative teaching methods, online platforms, multimedia resources, and mobile applications that support effective language acquisition. The article also discusses the advantages and challenges of digital education in the process of teaching English and emphasizes the importance of teachers’ digital competence. The findings demonstrate that the integration of digital technologies contributes to the development of communicative competence, independent learning, and critical thinking skills among learners.